The Availability of Strategic Implementation Requirements in the Private Banking Sector and its Reflection in Building Intelligent Organization: The Analytical Study of Employee’s Views in a Sample from Private Banking Sector in the Kurdistan Region of Ir - Abdullah, Da Roon; Wali, Ahlam (The Arab Journal of Administration, 2021)
This research aims to identify to which extant the requirements of strategic implementation are applied in the banking private sector in the KRG of Iraq and its role in building intelligent organizations. After reviewing the literature, the conceptual framework and the study models and hypothesis were written based on the Strategic implementation requirements and the dimensions of intelligent organizations. The questionnaire were designed for collecting the data, and were distributed to the research sample represented by the workers in the sample of private banks sector in the Kurdistan Region of Iraq including (331) workers. A number of tests were carried out before and after the distribution of questionnaire to verify their validity and reliability and to ascertain their validity in measuring the variables of study such as face validity, comprehensiveness, reliability, content validity, neutrality, internal consistency, as well as apply the normality to test the study data. Several statistical methods were used, including simple correlation analysis, simple linear regression and variance using SPSS package 20v. The results showed a positive relationship and effect between the variables and their dimensions. Based on the results, a number of recommendations were given regarding the need for the private banks to provide the requirements for strategic implementation in order to be able to survive and stable and thus become intelligent banks, as well as a set of other recommendations and its mechanisms.